2009
DOI: 10.1097/ico.0b013e3181971213
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Necrotizing Scleritis Resulting From Pseudomonas aeruginosa

Abstract: This is the first case report of infectious scleritis in the context of P. aeruginosa sepsis in the absence of corneal infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…2,5,11 Several reports have described atypical cases featuring a painfree presentation, normal visual acuity, lack of corneal infiltrates, normal intraocular pressure, and absence of anterior chamber reaction. 8,[45][46][47][48] Other uncommon manifestations include aqueous fistula formation in pneumococcal scleritis, inverse hypopyon in a case of pyomyositis with S. aureus scleritis, and spontaneous IS in immunocompromised patients with no history of ocular surgery or trauma. 5,32,49 Infectious scleritis may also masquerade as other diseases, including SINS, autoimmune scleritis, ocular tumors, orbital cellulitis, cavernous sinus thrombosis, and carotidcavernous fistula.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…2,5,11 Several reports have described atypical cases featuring a painfree presentation, normal visual acuity, lack of corneal infiltrates, normal intraocular pressure, and absence of anterior chamber reaction. 8,[45][46][47][48] Other uncommon manifestations include aqueous fistula formation in pneumococcal scleritis, inverse hypopyon in a case of pyomyositis with S. aureus scleritis, and spontaneous IS in immunocompromised patients with no history of ocular surgery or trauma. 5,32,49 Infectious scleritis may also masquerade as other diseases, including SINS, autoimmune scleritis, ocular tumors, orbital cellulitis, cavernous sinus thrombosis, and carotidcavernous fistula.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Bacterial or fungal invasion into the sclera is uncommon, accounting for less than 1% of all eye infections 2. Scleral infection can develop during progressive microbial keratitis or panophthalmitis3,4 and has rarely occurred in the absence of contiguous disease 5…”
Section: Introductionmentioning
confidence: 99%
“…It also has an ability to form a biofilm complex, which impedes its clearance by the immune-defense mechanism [ 14 ]. Various methods of treatment in patients with infectious Pseudomonas scleritis, including topical antibiotic eye drops only [ 8 ], adjunctive oral imipenem [ 9 ], adjunctive intravenous ceftazidime and aminoglycoside [ 10 ], adjunctive surgical debridement [ 11 ], adjunctive cryotherapy [ 12 ], and autologous perichondrium graft [ 13 ] have been reported in previous studies. A study by Codère et al [ 8 ] showed failure of medical treatment with topical antibiotic eye drops only.…”
Section: Discussionmentioning
confidence: 99%
“…The most common causative pathogen of infectious scleritis is Pseudomonas aeruginosa [ 2 , 5 , 6 , 7 ], a virulent organism that can produce protease. Previous studies have reported various treatments of infectious Pseudomonas scleritis with topical antibiotic eye drops only [ 8 ], adjunctive oral imipenem [ 9 ], adjunctive intravenous ceftazidime and aminoglycoside [ 10 ], adjunctive surgical debridement [ 11 ], adjunctive cryotherapy [ 12 ], and autologous perichondrium graft [ 13 ]. This study demonstrated another option of treatment in a patient with infectious Pseudomonas scleritis.…”
Section: Introductionmentioning
confidence: 99%